National Bioethics Commissions as Educators - Lee, Lisa M. (The Hastings Center report, 2017)
As has become tradition, executive directors of United States’ presidential bioethics committees offer reflections about their experience shortly after the orderly shutdown of the commission staff. After the records are filed according to government records regulations; after all the staff members, who are hired into temporary positions that must be renewed every two years, have secured permanent employment; after preparations are made to ensure that the next commission staff (should there be one) has a budget and standard operating procedures in order to begin its work in a timely manner; after the lights are turned out for the last time, the executive director makes the final climb up the stairs into the sunlight and reflects on the whirlwind. There is much about my work with the Presidential Commission for the Study of Bioethical Issues that deserves comment, but one aspect of the commission that has been especially valuable to me is its work to educate the nation on bioethical issues. This is, moreover, a contribution in which the commission staff was central, and it is one that, as an ethics educator myself, I will cherish deeply.